The role of bariatric surgery in the treatment of diabetes. (May 2014) - Tham, Ji Chung; Howes, Noah; le Roux, Carel W.
The obesity epidemic contributes to approximately 44% of the world's type 2 diabetes burden. Bariatric surgery is an effective treatment for type 2 diabetes mellitus in patients with morbid obesity as it improves glycaemia, blood pressure, lipids and inflammation. This review describes the evidence supporting the addition of bariatric surgery to the treatment algorithms used by diabetologists. We emphasize the need to view bariatric surgery as an adjuvant therapy which should not be used instead of but rather together with best medical therapy.